Pengaruh Literasi Keuangan, Pembelajaran di Perguruan Tinggi dan Pengalaman Bekerja Terhadap Perilaku Keuangan Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang - Atiqoh, Nihaya Nazilatul; Sudaryanti, Dwiyani; Hariri, Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to find out how financial literacy, college learning and work experience influence student financial behavior. This research is a type of quantitative research, using 72 Accounting students class of 2019 at the Faculty of Economics and Business, Islamic University of Malang as samples in this study. Data collection in this study used a questionnaire using a Google form with a Likert scale of 4 points, namely 1 strongly disagree, 2 disagree, 3 agree and 4 strongly agree. Based on the results of research on Accounting study program students class of 2019, it was found that financial literacy obtained a significance value of 0.013 <0.05, then H¬0 was rejected and H1a was accepted, learning variables in tertiary institutions obtained a significance value of 0.039 <0.05, so H0 was rejected and H1b is accepted, the work experience variable obtains a significance value of 0.000 <0.05, then H0 is rejected and H1c is accepted. Based on this explanation, it can be said that financial literacy, learning in college and work experience have a significant effect on student financial behavior.Keywords: Financial Literacy, Learning in Higher Education, Work Experience, Student Financial Behavior